Development of Mobile Learning-Based Gamification to Improve Effectiveness and Motivation in Local History Learning at Universitas 17 Agustus 1945 Banyuwangi: Pengembangan Gamifikasi Berbasis Mobile Learning untuk Meningkatkan Efektivitas dan Motivasi Pembelajaran Sejarah Lokal di Universitas 17 Agustus 1945 Banyuwangi - Romadloni, Sahru; Rachman, Adytira; Pradana, Dian Arief (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research is motivated by the low motivation and learning outcomes of students in the Local History course, which has so far been dominated by conventional methods such as lectures and rote memorization, making the learning process monotonous and less engaging. To address this issue, the study aims to develop a gamification-based learning medium by utilizing Quiziz and Wayground applications as an innovative strategy to enhance the effectiveness, interactivity, and motivation of students in learning history. The research method employed was Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The analysis phase focused on identifying students’ needs and the shortcomings of conventional learning methods, while the design phase formulated appropriate gamification elements for local history content. The development process produced a prototype that was validated by media and content experts, with average scores of 4.20 and 3.95, respectively, categorized as good. The implementation stage was carried out through a small-scale trial with 10 students and a large-scale trial with 30 students, resulting in positive responses with average scores of 4.05 for the small group and 4.18 for the large group. Furthermore, the effectiveness test was conducted by involving 30 students in the experimental class and 30 students in the control class. The results showed a significant difference between the two groups, where the experimental class achieved an average score of 82.00, while the control class achieved only 74.20, with an independent t-test result of p = 0.000 < 0.025, indicating that gamification-based mobile learning is effective in improving students’ learning outcomes. The novelty of this research lies in the integration of gamification with Local History content through mobile applications that allow students to access learning materials anytime and anywhere, thus making the learning of history not only more enjoyable but also strengthening their understanding of local values and nationalism.